Novel association between FOXO3 rs2232365 polymorphism and late-onset preeclampsia: a case-control candidate genetic study - Xuefeng Pan; Benjie Wei; Hong Wang; Lingyu Ma; Zhaoli Du; Ying Chen (BMC, 2020)
Abstract Background Both genetic susceptibility and dysregulated lipid metabolism are important susceptibilities to preeclampsia. In the study, we devote to investigate the associations of FOXO3 and TLR7 genetic polymorphisms with preeclampsia in a Chinese population. Methods This case-control study involved 335 Han Chinese pregnant women, including 177 pregnant women with preeclampsia and 158 healthy controls. The preeclampsia group was further sub-grouped into early-onset preeclampsia (EOPE, n = 70)and late-onset preeclampsia (LOPE, n = 107. Three single nucleotide polymorphisms (SNPs), including FOXO3 (rs2232365, rs3761548), and TLR7 rs3853839 were genotyped by multiplex PCR for targeted next-generation sequencing. The χ2 test and multiple interaction effect analyses were performed to determine the association of three SNPs with serum lipid levels and thyroid function in women with preeclampsia. Results The genotype (CC vs. TT + CT) distribution of rs2232365 revealed a significant association with LOPE (P = 0.004, odds ratio = 3.525 (0.95 CI: 1.498-8.164)). No significant difference was found in the genotype and allele frequencies of rs3761548 and rs3853839 between controls and cases (P > 0.05). Moreover, the genotype CT/TT of rs2232365 was significantly correlated with increased TG/HDL levels in the LOPE group (p = 0.014). Conclusions The polymorphisms of rs2232365 are associated with the risk of LOPE and may modulate TG/HDL levels in pregnant women with LOPE.